Peran Profitabilitas Dalam Memoderasi Hubungan Antara Kualitas Audit Serta Alokasi Pajak Antar Periode Terhadap Kualitas Laba Entitas Perusahaan - Pardomuan Ritonga (LPPM Universitas Multi Data Palembang, 2023)
This research is aim to analyze the influence of audit quality and Allocation of Inter-period Tax on the firm’sprofitability and implications with earnings quality. This type of research isquantitative. The research population is sub-sectors of finance company listed in the Indonesia Stock Exchange in2015-2019. The sampling method using purposive sampling technique is counted 16 companies. The method ofanalysis using linear regression analysis and sobel test. These results indicate that audit quality and Allocation ofInter-period Tax have significant effect simultaneously on the profitability of firms as long as audit quality andAllocation of Inter-period Tax have no significant effect simultaneously on the earnings quality. The partial testresults showed that audit quality has effect while Allocation of Inter-period Tax has no effect to the profitability offirms. However, audit quality and Allocation of Inter-period Tax have no indirect effect to the earnings qualitythrough profitability of firms